ENVIRONMENTAL VALUES IN THE POETRY ANTHOLOGY MATA SUKMA, MATA CINTA BY DINULLAH RAYES: AN ECOCRITICAL ANALYSIS - Sultan Bahanan; Iwan Jazadi (STKIP Paracendekia NW Sumbawa, 2025)
This study investigates the representation of environmental values in the poetry anthology Mata Sukma, Mata Cinta by Dinullah Rayes through a qualitative ecocritical lens. Ecocriticism, which explores the interplay between literature and the environment, provides a framework for examining how poetic diction reflects ecological consciousness. The research employs a descriptive qualitative approach, analyzing 147 environment-related words that appear frequently (≥5 occurrences) across the anthology. These dictions are categorized into three environmental domains: land (e.g., pohon, batu), water (e.g., laut, air, muara), and air/outer space (e.g., bulan, bintang). Findings reveal that the selected lexical items function not only in literal contexts but also convey metaphorical, symbolic, and emotive associations with nature. This duality suggests a layered ecological awareness embedded in the poetic language. The study contributes to the growing discourse on literary ecocriticism in Indonesian literature, offering insights into how poetry can cultivate environmental sensitivity.